Improving the stability of perovskite solar cells under harsh environmental conditions. (15th May 2020) - Sidhik, Siraj; Rosiles Pérez, Christopher; Serrano Estrada, Mario Alberto; López-Luke, Tzarara; Torres, Alejandro; De la Rosa, Elder
Highlights: High Purity Lead Sulfide (PbS) quantum dots synthesized by Nano-emulsion method. PbS QDs were utilized as the electron transport material in perovskite solar cells. PbS QDs used as a buffer layer for avoiding the ingress of humidity into the perovskite devices. The perovskite device shows record stability under high humidity of 70%. Abstract: In this work, it is reported for the first time the synthesis of high-purity Lead Sulfide (PbS) quantum dot (QD) using the nano-emulsion method assisted by an ultrasonic bath, which was tested as a hole transporting material (HTM) in perovskite devices. Further, these PbS QDs were introduced in CH3 NH3 PbI3 based perovskite device, between the perovskite layer and the HTM to enhance its stability against humidity. The hydrophobic nature of the PbS protects the perovskite by preventing the diffusion of water into the device. To compare the effect, the perovskite devices with and without the layer of PbS QDs were tested under high humidity conditions ( 70%) without encapsulation. The pristine perovskite devices completely degraded after a span of 10 days, whereas the devices with PbS QDs showed huge resistance to humidity by retaining 76% of its initial efficiency after a span of 60 days. Such enhanced stability under adverse environmental conditions has never been reported. Also, these results would open up a new insight of PbS QDs being utilized as a barrier against high humid conditions for making air-stable devices.